Sustainable Development and Business Strategies: An International Higher Education Experience - Issa, Theodora (Society for Global Business & Economic Development (SGBED), 2011)
This paper reports on development and facilitation of a unit (course) on ‘Sustainable development and Business Strategies’ (SDBS). SDBS was developed in Australia for delivery to international students originated from different countries gathered in Europe. SDBS allowed students to cultivate a new perspective towards change, outlining a new strategy through innovation in an ever changing, uncertain and contemporary ‘risk society’ (Beck, 2002). The topic of sustainable development and business strategies has gained momentum at governments, international organizations, business and higher education levels. To understand the multidisciplinary nature of this vast topic, which, in part, touched on ethical issues, sustainability and strategic development in contemporary business; SDBS was designed to allow students the engagement in class discussions, arguments and debates, sharing their unique international experiences, throughout which transformation and modification in their mindsets was witnessed.This was measured through class discussions and assessments that were designed in consultation with the European partners. This paper starts with literature review on the concepts under study, an insight into SDBS’s development and concludes with analysis of some of the quantitative and qualitative data collected from 51 students over two periods. This is coupled with facilitator’s personal reflection. Though this paper has its limitations, yet it is a small step forward towards developing an international perspective for teaching these rather importance issues to business and management students.